Whistle While You Work - Erdogan, Berrin; Bauer, Talya N.; Truxillo, Donald M.; Mansfield, Layla R. (Journal of Management, 2012)
Life satisfaction is a key indicator of subjective well-being. This article is a review of the multidisciplinary literature on the relationship between life satisfaction and the work domain. A discussion of top-down and bottom-up theories of life satisfaction is included, and the literatures on work-related antecedents of life satisfaction, the proximal mediators (quality of work life, quality of nonwork life, and feelings of self-worth), and consequences of life satisfaction were reviewed. A meta-analysis of life satisfaction with respect to career satisfaction, job performance, turnover intentions, and organizational commitment was performed. Each major section of the article concludes with a future opportunities subsection where gaps in the research are discussed.